2013
DOI: 10.6002/ect.2012.0110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Marrow Mesenchymal Stem Cell Transplant on Synovial Proliferation in Rats With Type II Collagen-Induced Arthritis

Abstract: Objectives: To investigate the influence and mechanism of bone marrow mesenchymal stem cell transplant in the synovial proliferation of type II collagen-induced arthritis. Materials and Methods: From the bone marrow of Sprague-Dawley rats, mesenchymal stem cells were isolated and expanded. Forty rats were randomly divided into 5 groups: normal control, early mesenchymal stem cell treatment, late mesenchymal stem cell treatment, early collagen-induced arthritis control, and late collagen-induced arthritis contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…reported that MSCs do not have any effects in CIA mice31. However, various studies report beneficial effects of MSCs in CIA mice323334353637. The use of various cell strains and differences in the infused cell number or the administration route make it difficult to compare and interpret the inconsistent results of previous studies38.…”
Section: Discussionmentioning
confidence: 99%
“…reported that MSCs do not have any effects in CIA mice31. However, various studies report beneficial effects of MSCs in CIA mice323334353637. The use of various cell strains and differences in the infused cell number or the administration route make it difficult to compare and interpret the inconsistent results of previous studies38.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the therapeutic effects of allogeneic or xenogenic MSC transplantation in CIA-mice 30 31 32 33 34 35 36 40 41 . Nevertheless, the underlying mechanisms are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent progenitor cells that can differentiate into tissues of mesenchymal lineage, including bone, cartilage and adipose tissue 27 28 29 . Several studies have reported therapeutic effects of allogenic or xenogenic MSC transplantation in CIA mice 30 31 32 33 34 35 36 . However, the underlying molecular basis of these effects is not fully understood.…”
mentioning
confidence: 99%
“…Numerous studies have observed improved efficacy when the MSC infusion was performed during the early phases of the disease (47% and 25% in the onset and in the established phase of the disease, respectively) rather than at pre-onset (19%) or during chronic phases (9%) of the disease, although promising results in terms of efficacy were observed in all instances ( Fig. 5 a, Supplementary Tables 1 and 2) [ [33] , [34] , [35] , [71] , [72] , [73] , [74] ]. In contrast, the completed RA clinical trials with MSC-based therapy have been conducted in very refractory RA patients with a long history of the disease which may have hindered the beneficial effects of MSC-based therapy in the clinic.…”
Section: Msc Dosage and Time Of Infusionmentioning
confidence: 99%